Analysis on the Influence of Fault Protection Coal Pillar Size on Rockburst. (6th May 2021) - Xin, Hengqi; Li, Qinghai; Liu, Li; Liu, Zhijun; Hou, Junmin
Abstract : Compared with other types of rockburst, fault rockburst releases the most energy and brings the hugest damage to the stope. Reasonable fault protection coal pillar can effectively prevent and control the occurrence of fault rockburst. Reasonable fault protection coal pillar (FPCP) can prevent and control the occurrence of fault rockburst effectively. Based on the engineering background of No. 7 mining area in a coal mine, this paper analyzes the reasonable coal pillar size on both sides of normal fault. Combined with the geological conditions in site, through the mechanical analysis of coal pillar stability, it is calculated that the critical FPCP size is 27.9 m for the working face in the upper wall and 39.0 m for the working face in the footwall. Through numerical simulation analysis, it is found that with the critical size of FPCP, the stress concentration coefficient in front of the upper wall working faces and footwall working faces is about 1.59. When the size of FPCP is smaller than the critical one, the difference of stress concentration coefficient between the two working faces (upper wall working face and footwall working face) is large, and the difference becomes larger and larger with the decrease of coal pillar size. When the size of FPCP is larger than the critical one, the difference of stress concentration coefficient between the two working faces (upper wall working face and footwall working face) is small, and the stress concentration coefficient of the two faces tends to be equal with the increase of coal pillar size. The rationality of coal pillar size is verified by field application, which provides a basis for the selection of FPCP in subsequent mining under similar conditions.